Qualitative biomechanical principles for application in coaching - Knudson, D. (Sports Biomechanics, 2007)
Many aspects of human movements in sport can be readily understood by Newtonian rigid-body mechanics. Many of these laws and biomechanical principles, however, are counterintuitive to a lot of people. There are also several problems in the application of biomechanics to sports, so the application of biomechanics in the qualitative analysis of sport skills by many coaches has been limited. Biomechanics scholars have long been interested in developing principles that facilitate the qualitative application of biomechanics to improve movement performance and reduce the risk of injury. This paper summarizes the major North American efforts to establish a set of general biomechanical principles of movement, and illustrates how principles can be used to improve the application of biomechanics in the qualitative analysis of sport technique. A coach helping a player with a tennis serve is presented as an example. The standardization of terminology for biomechanical principles is proposed as an important first step in improving the application of biomechanics in sport. There is also a need for international cooperation and research on the effectiveness of applying biomechanical principles in the coaching of sport techniques.